Implementasi Program BERDES (Bersih Desa) sebagai Upaya Menumbuhkan Kesadaran Peduli Lingkungan di SD Negeri 2 Demulih - Wayan Ariawan Warestana; Luh Made Dwi Wedayanthi (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
This study aimed to investigate the implementation of the BERDES (Bersih Desa) Program as an innovative strategy to foster environmental awareness among elementary school students at SD Negeri 2 Demulih. The program was designed using a participatory approach based on the Participatory Action Learning Sistem (PALS) method, which engaged students as active participants in identifying problems, planning, executing, and evaluating real actions in their school and local community environments. The research found that active student involvement in cleaning activities, waste management socialisation, and collective reflection significantly enhanced positive attitudes and social responsibility towards environmental conservation from an early age. Despite challenges such as limited frequency of program activities and common misconceptions about waste classification (organic, inorganic, residual), the BERDES program successfully served as an effective educational tool that embedded environmental care values among rural youth. The findings emphasised the critical role of schools as centres for environmental character education that combine theoretical knowledge with practical engagement to address real environmental issues.